The investigation analysis as evidence in a criminal trial - Kościelniak-Marszał, Miłosz (The Opole Studies in Administration and Law, 2017)
The investigation analysis consists in performing a series of ordered actions completed according to the established order and aimed at reaching the most precise and logical conclusion based on the information available. Thus, analysts’ actions focus on the study of actual and potential relationship between individual pieces of information which may be relevant for determination of a crime and its perpetrator. Their job involves processing and selecting information possessed by the procedural authority, according to specific criteria in order to present it in the form that will help recreate the chain of events and draw conclusions. Although the investigation analysis has not been mentioned in the Code of criminal procedure, one must agree that as a method of establishing evidence it should find its place in the criminal proceedings. This is because the rejection of new evidence would be nothing else but resignation of law enforcement authorities from adapting to a new situation within the scope of crime. However, we must make sure that introduction of the results of the investigation analysis into criminal proceedings does not negatively affect the principles of the proceedings, in particular with regard to a fair trial and the right to defence, and in no way does it connect with violation of the related procedural guarantees.